Design and Development of Offshore Mobile Electricity Generation System using Damping Wave Energy Converter - Wong, Yi Hong (2019)
This research is intended to study the feasibility of harnessing ocean wave energy using a damping wave energy converter (DWEC), a type of passive damping device that operates similarly to a tuned liquid column damper (TLCD) that is designed to reduce externally induced vibration at a designated frequency range, albeit with the ability to harvest wave energy simultaneously. The proposed DWEC can be integrated with a floating offshore structure to operate as a vibration suppressing device through reduction of dynamic response of the structure due to wave impact and simultaneously generating electricity through the oscillating flow of stored liquid within the DWEC. The constructed DWEC prototype is tuned according to the theoretical study and tested with two different sets of design using a shaking table with a set of predetermined frequency range and a third set that is simulated using commercial CFD software ANSYS Fluent. With that, the amount of energy extractable from the oscillating water motion within the DWEC column are studied as well.